2019
DOI: 10.1002/ange.201903631
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a [4+6] Salicylbisimine Cage to Chemically Robust Amide Cages

Abstract: In recent years, interest in shape‐persistent organic cage compounds has steadily increased, not least because dynamic covalent bond formation enables such structures to be made in high to excellent yields. One often used type of dynamic bond formation is the generation of an imine bond from an aldehyde and an amine. Although the reversibility of the imine bond formation is advantageous for high yields, it is disadvantageous for the chemical stability of the compounds. Amide bonds are, in contrast to imine bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 80 publications
(20 reference statements)
0
10
0
1
Order By: Relevance
“…For instance, it was recently demonstrated that applying a Pinnick oxidation reaction could convert a dynamic imine cage into a chemically stable amide cage. 57 This might provide a feasible method for making macrocycles or cages containing amide hydrogen-bond donors as anion receptors.…”
Section: Llmentioning
confidence: 99%
“…For instance, it was recently demonstrated that applying a Pinnick oxidation reaction could convert a dynamic imine cage into a chemically stable amide cage. 57 This might provide a feasible method for making macrocycles or cages containing amide hydrogen-bond donors as anion receptors.…”
Section: Llmentioning
confidence: 99%
“…To increase the chemical stability of imine cages, reduction to amines was reported but is often accompanied by a higher degree of conformational freedom, leading to loss of porosity. Twelvefold Pinnick oxidation was shown to again lead to highly porous and chemically robust amide cages that are also stable over a large pH range, even allowing further post modification by means of direct bromination [16c] . All sorption data for this class of compounds is presented in Table 2.…”
Section: Porous Organic Cagesmentioning
confidence: 99%
“… The parent salicylbisimine Tri 4 Di 6 POC SC1 by the group of Mastalerz underwent various reactions for exo ‐functionalization. a) After post‐synthetic methylation, cage Me‐SC1 underwent Pinnick oxidation, for transformation into the chemically robust amide cage SC2 ; [16c] b) reaction of the parent POC SC1 by twelvefold Povarov reaction utilizing phenylacetylene gave quinoline POC SC3 in one step in 25 % yield; [16b] c) and d) a range of salicyldialdehydes 6 & 8 , bearing various alkyl substituents can be used to generate exo ‐functionalized salicylbisimine POCs, that allowed for successful control of the extrinsic pores in crystalline states [16e] . Hydrogen atoms and solvent molecules are omitted for clarity, space‐filling view including hydrogen atoms for exo ‐groups.…”
Section: Porous Organic Cagesmentioning
confidence: 99%
“…For example, Cooper and co-workers converted the imine in CC3 to an amine, and the resulting structure can be stable over a wide pH range (pH = 1.7–12.3) 37 . Mastalerz et al reported the transformation of imine bonds in [4 + 6] salicylimine cage into chemically robust amide bonds via Pinnick oxidation 45 . Furthermore, they utilized the Povarov reaction and the subsequent oxidation to transform the salicylimine cage into a quinoline cage which is stable under harsh acidic and basic conditions 46 .…”
Section: Introductionmentioning
confidence: 99%